Analysis of public discourse on heart transplantation in Japan using social network service data. Issue 1 (11th November 2017) - Nawa, N.; Ishida, H.; Suginobe, H.; Katsuragi, S.; Baden, H.; Takahashi, K.; Narita, J.; Kogaki, S.; Ozono, K.
Abstract : The clarification of public concerns regarding heart transplantation is important for improving low organ donation rates in Japan. In the present study, we used the Twitter data of 4986 tweets (between August 2015 and January 2016) and 1429 tweets (between April 2016 and May 2016) to analyze public discourse on heart transplantation in Japan and identify the reasons for low organ donation rates. We manually categorized all tweets relevant to heart transplantation into nine categories and counted the number of tweets in each category per month. During the study period, the most popular category of tweets was related to the media, followed by money (tweets questioning or even criticizing the high price of fundraising goals to go overseas for heart transplantations), while some tweets were misconceptions. We also conducted a sentiment analysis, which revealed that the most popular negative tweets were related to money, while the most positive tweets were related to reports on the favorable outcomes of recipients. Our results suggest that listening to concerns, providing correct information (particularly for some misconceptions), and emphasizing the outcomes of recipients will facilitate an increase in the number of people contemplating heart transplantation and organ donation. Abstract : Analysis of public discourse on heart transplantation in Japan using social network service data suggests that people have positive as well as negative concerns about heart transplantation.